2013
DOI: 10.1371/journal.pone.0057248
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspirates CYFRA 21-1 is a Useful Tumor Marker for Detecting Axillary Lymph Node Metastasis in Breast Cancer Patients

Abstract: IntroductionTo assess whether the value of CYFRA21-1 in the aspirates of ultrasonography-guided fine-needle aspiration biopsy (US-FNAB) can contribute to improving the performances of US-FNAB in the diagnosis of axillary lymph node (LN) metastasis in breast cancer patients.MethodsUS-FNAB was performed in 156 axillary LNs in 152 breast cancer patients (mean age: 51.4 years, range: 17–92 years). Concentrations of CYFRA21-1 were measured from washouts of the syringe used during US-FNAB. Tumor marker concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 37 publications
1
17
0
2
Order By: Relevance
“…For surveillance of patients with diagnosed breast cancer, the most widely used serum markers are CA 15-3 and CEA which, in combination with other clinical parameters, could have clinical significance. 12 Serum CYFRA 21-1, the most sensitive tumor marker used in monitoring non-small cell lung cancer 10,11 has been reported to be detected in the peripheral blood from patients with metastatic breast cancer. 9 The present study showed that, serum CYFRA21-1 in breast cancer patients before surgery was highly elevated than that in control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For surveillance of patients with diagnosed breast cancer, the most widely used serum markers are CA 15-3 and CEA which, in combination with other clinical parameters, could have clinical significance. 12 Serum CYFRA 21-1, the most sensitive tumor marker used in monitoring non-small cell lung cancer 10,11 has been reported to be detected in the peripheral blood from patients with metastatic breast cancer. 9 The present study showed that, serum CYFRA21-1 in breast cancer patients before surgery was highly elevated than that in control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about this tumor marker for breast cancer. [7][8][9] Serum CYFRA 21-1, the most sensitive tumor marker used in monitoring nonsmall cell lung cancer 10,11 has been reported to be detected in the peripheral blood from patients with metastatic breast cancer and proposed to be used in monitoring disease relapse and treatment response in breast cancer patients. 9 The aim of the present study was to evaluate the clinical significance of serum CYFRA21-1 in patients with primary breast cancer by analyzing the correlation between serum CYFRA21-1 titers, clinicopathological factors and prognosis in comparison with serum CA15.3 and CEA tested in the same samples.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31] Many researchers have reported reliable methods for ALN staging preoperatively. 9,17,[31][32][33][34][35][36][37][38][39][40] Axillary sonography has been widely used as for preoperative evaluation of ALNs in patients with breast cancer because it can be performed simultaneously with breast sonography without much additional time and cost. 41 However, axillary sonography is operator dependent, and the detection and diagnosis of suspicious LNs by axillary sonography can be limited, especially in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of FNA can increase the specificity and PPV to 90% to 100%, 7,36,[42][43][44][45] even if FNA generates false-negative results ranging from 11.6% to 24%. 9,34,[39][40][41][45][46][47] Positron emission tomography-CT is another method that can be used for preoperative ALN staging; however, it was reported to have a lower spatial resolution and a wide range of false-positive rates (0%-15.3%). 11,[15][16][17]29,[48][49][50] Therefore, in this study, we intended to compare the diag- nostic performance of 3 modalities: sonography, sonographically guided FNA, and FDG PET-CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation